Zintegrowany program operacyjny rozwoju regionalnego - kierunki wsparcia a pożądane efekty transformacji przestrzeni w woj. zachodniopomorskim - Filipiak, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article presents an influence of ZPORR on creating the competitiveness and development of Zachodniopomorskie Province. The author discuses: idea of the program, goals and directions of the allocation of its funds. The author analyzes the official data concerning the implementation of the program in the Zachodniopomorskie Province. In the end, conclusions are formulated focusing on the advisable effect of growing competitiveness and development of Zachodniopomorskie Province. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 195-207